Role of Scientific Research for Lecturers of Current Universities - Van Thang, Msc. Pham; Trong Thanh, MSc. Vu (International Journal of Humanities and Education Development (IJHED), 2024)
Scientific research for university lecturers plays an important role in training creative thinking ability, research capacity and scientific working style for researchers. This contributes to clarifying some scientific issues and solving practical problems that arise in order to improve the quality of teaching. This article focuses on analyzing some issues about the role of scientific research for university lecturers today.